Kinerja Lingkungan, Dewan Komisaris Independen dan Pengungkapan Corporate Social Responsibility: Tinjauan pada Konteks Perusahaan Manufaktur Sub Sektor Industri Dasar dan Kimia - Muhammad Rinaldi; Sitti Rahma Sudirman; Melda Aulia Ramadhani (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
The objective of this research is to acquire empirical proof regarding the impact of Environmental Performance and Independent Board of Commissioners on Corporate Social Responsibility (CSR) Disclosure. The methodology adopted for sample selection is Purposive Sampling, encompassing a sample size of 18 companies enlisted on the Indonesia Stock Exchange and engaged in PROPER from 2020 to 2022. Findings from this investigation reveal that while Environmental Performance does not exert influence on CSR Disclosure, the presence of an Independent Board of Commissioners yields a positive impact on CSR disclosure.